2017
DOI: 10.1002/gps.4837
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fear of falling and fall history on disability incidence among older adults: Prospective cohort study

Abstract: Fear of falling could be a simple and useful predictor of disability incidence in community-dwelling older adults. Identifying and decreasing fall risk factors may prevent fall-related injuries, but excessive FOF may be associated with increased risk of disability incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 28 publications
2
27
0
9
Order By: Relevance
“…To our knowledge, this is the first study to compare the prevalence and factors of FOF among community‐dwelling older adults from Latin America and Europe. Consistent with previous findings (Lavedan et al, ; Lee, Oh, & Hong, ; Makino et al, ), the average score for FOF was extremely high in three‐quarters of the studied sample. However, high FOF was much more prevalent among Portuguese participants.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to compare the prevalence and factors of FOF among community‐dwelling older adults from Latin America and Europe. Consistent with previous findings (Lavedan et al, ; Lee, Oh, & Hong, ; Makino et al, ), the average score for FOF was extremely high in three‐quarters of the studied sample. However, high FOF was much more prevalent among Portuguese participants.…”
Section: Discussionsupporting
confidence: 92%
“…Fear of fall was assessed by close-ended a question phrased as: "Are you afraid or concerned about falling while performing activities of daily living (ADL)? " [20]. Visual impairment (in any eye); significant loss of vision on which Snellen's chart reading is less than 6/12 to no light perception, Mild visual impairment; presenting with a visual acuity of less than 6/12(20/40) greater than or equal to 6/18(20/60).…”
Section: The Operational Definitionmentioning
confidence: 99%
“…As a recent systematic review by Schoene et al [15] confirmed, not only falls but also fall-related risk factors like fear of falling (FoF) influence HrQoL negatively. In the past, FoF was considered as consequence of falls, but nowadays FoF is considered as an independent predictor of disability or HrQoL, independent of a prior fall experience [15,16]. The prevalence of FoF in the population aged 65 years and above varies widely, with the majority of studies reporting a prevalence between 20 and 85% depending on sample characteristics and the measurement used to assess FoF [15,17].…”
Section: Introductionmentioning
confidence: 99%